1982
DOI: 10.1007/bf00313403
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cavernous haemangioma (intradural-extramedullary) underlying repeated subarachnoid haemorrhage

Abstract: Within a period of 13 months a 24-year-old male student experienced four attacks of subarachnoid haemorrhage. An intradural-extramedullary haemangioma at the level of the second thoracic segment was found to be the cause of the repeated bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Cauda equina nerve root is a very rare location. 4,[9][10][11][12][13][15][16][17][18][19][21][22][23][24][25][26] Pagni et al 15 reviewed all intradural cavernous angioma of the spine described in the literature. They concluded that subdural extramedullary cavernous angiomas are the most rare of the cavernomas with only 10 cases documented between 1903 and 1990.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cauda equina nerve root is a very rare location. 4,[9][10][11][12][13][15][16][17][18][19][21][22][23][24][25][26] Pagni et al 15 reviewed all intradural cavernous angioma of the spine described in the literature. They concluded that subdural extramedullary cavernous angiomas are the most rare of the cavernomas with only 10 cases documented between 1903 and 1990.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Intradural-extramedullary location is very rare, with only 23 cases reported in the literature accessible to us by Medline Research. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] We describe a case of cavernoma located within the boundaries of a lumbar nervous root and we discuss its clinical, radiological, and surgical findings.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, only several case reports have described the presence of dural or perimedullary arteriovenous fistulas (DAVF) [2,10,14,17,22,28,31,44,45,48] and cavernous malformations [1,4,7,15,20,[25][26][27]42] as a cause of angiogram-negative SAH. The incidence of a spinal origin of SAH has been reported on in only three articles: Walton [47] described three cases, including one spinal AVM in 312 angiogram-negative SAH, resulting in a incidence of SVM of less than 1 % of total SAH.…”
Section: ■ Svm Incidence In Sahmentioning
confidence: 99%
“…The course of postoperative recovery was uneventful, and Review of the literature Table 1 provides a summary of the 23 reported surgically treated cases of spinal intradural extramedullary CAs, including the present report. 1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The ages of the patients are between 22 and 67 years, with an average of 43.3 year (Table 1). 65.2% of the patients presenting with intradural extramedullary spinal CAs are males.…”
Section: Case Reportmentioning
confidence: 99%